21 Effect of Corn Silage Inclusion Rate on Live Growth Performance, Carcass Characteristics, Net Energy Utilization and Beef Production Per Hectare in Feedlot Finishing Steers. (7th May 2021) - Buckhaus, Elizabeth M; Smith, Zachary K
Abstract: Maine-Anjou × Angus beef steers (n = 156; initial BW 366 ± 37.2 kg) were used in a finishing experiment at the Ruminant Nutrition Center in Brookings, SD. Steers were weighed on 2 consecutive days and assigned into 5 weight blocks (replicate pens). Treatments were arranged in a 2 × 2 factorial, 2 types of implants and 2 dietary treatments. Dietary treatments consisted (DM basis) of 1) 15% (CS15) or 2) 30% corn silage (CS30). Other ingredients consisted of DRC, HMC, liquid supplement and a dry supplement. The NEm, NEg and CP of CS15 was 94.8 Mcal/45.4 kg, 64.0 Mcal/45.4 kg and 12.7% and 91.2 Mcal/45.4 kg, 61.1 Mcal/45.4 kg, and 12.5% respectively (DM basis) for CS30. Bunks were managed using a slick bunk approach and all diets contained (DM basis) 33 mg/kg monensin sodium. Corn silage yield was assumed to be 45.7 Mg/ha and corn grain yield was calculated to be 10.2 Mg/ha. Beef production per hectare was calculated as (carcass adjusted final BW – initial BW)/hectare. No interaction between diet and implant (P ≥ 0.16) was detected for any variables. Final BW, ADG, and G:F were increased (P ≤ 0.02) by 2.2%, 6.5% and 7.2% respectively for CS15. Observed NE and the ratio of observed-to-expected NE for maintenance and gain was not influenced (P ≥ 0.15) by treatment. Dressing percent (64.52 vs. 63.47 ± 0.250; P = 0.01) and HCW (379 vs. 371 ± 13.1 kg; P = 0.02) were greater in CS15. Beef production per hectare was not impacted (P = 0.76) by feeding greater levels of corn silage. Feeding CS15 resulted in greater carcass-adjusted growth performance and HCW. No differences in beef produced per hectare of crop land means producers can feed greater inclusions of corn silage to finishing cattle without impacting carcass quality or beef production.